2017
DOI: 10.21873/anticanres.11607
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Splenic Metastasis Αfter Surgically-treated Cervical Cancer – A Case Report and Literature Review

Abstract: Abstract. Background Cervical cancer remains one of the most common gynecologic malignancies worldwide; although association of oncologic treatment is widely performed, a number of cases will develop, at a certain moment, distant metastases (1, 2). Unfortunately, most patients in this situation will be diagnosed with disseminated secondary lesions, being candidates only for palliative treatment. In rare cases, solitary metastases have been reported, transforming the patient into the perfect candidate for re-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…However, a wide implementation of screening tests has led to a decrease in the incidence of the malignancy in the last decades. In our country, unfortunately, cervical cancer still represents a significant health problem affecting women in all ages (8)(9)(10)(11)(12)(13). When it comes to the possibility of association of these two entities, different theories have been proposed so far.…”
Section: Discussionmentioning
confidence: 99%
“…However, a wide implementation of screening tests has led to a decrease in the incidence of the malignancy in the last decades. In our country, unfortunately, cervical cancer still represents a significant health problem affecting women in all ages (8)(9)(10)(11)(12)(13). When it comes to the possibility of association of these two entities, different theories have been proposed so far.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the literature, the incidence of splenic metastases from cervical cancer ranged from 1/92 to 8/108 in autopsy cases 4 . To the best of our knowledge, only 17 cases of splenic metastasis resulting from cervical cancer have been reported in the literature (Supplementary Table ), including ours 5‐15 . The stages of the 17‐splenic metastasis retrieved from the literature were as follows: 11.76% (2/17) in stage IB, 23.53% (4/17) in stage IIA, 47.06% (8/17) in stage IIB, 5.88% (1/17) in stage IIIB, and 5.88%(1/17) in stage IVA.…”
Section: Discussionmentioning
confidence: 98%
“…14 According to a case report by Dixit et al, which reported splenic metastasis at 17 months after completion of the oncological treatment for squamous cell cervical cancer, only 11 cases had been published before, with their case being the 12 th reported ever. 6 Most of the literature available until today focuses on scattered case reports, as well as autopsy series between 20-80 years ago. Lack of information is thought to be due to selection bias and an overall decrease in the number of subjects undergoing autopsy.…”
Section: Discussionmentioning
confidence: 99%